Teaching the Nature of Science Through Biodiesel Synthesis from Waste Cooking Oil: A Literature Review with Experimental Insights - Juan Peña-Martínez; Jessica Beltrán-Martínez; Ana Cano-Ortiz; Noelia Rosales-Conrado (Sustainable Chemistry, 2025)
This work reviews the use of biodiesel synthesis experiments in science education, emphasising their potential for explicit nature of science (NOS) teaching. Through a literature review and experimental insights, it highlights how transesterification of waste cooking oil (WCO) with a basic catalyst can serve as an educational tool. While biodiesel reaction conditions are well-documented, this study presents them in a pedagogical context. Simple viscosity and density measurements illustrate empirical analysis, while a design of experiments (DoE) approach using a Hadamard matrix introduces systematic optimisation and scientific reasoning. By integrating biodiesel synthesis with explicit NOS instruction, this work provides educators with a framework to foster critical thinking and a deeper understanding of scientific inquiry. Additionally, this approach aligns with green chemistry principles and resource efficiency, reinforcing the broader relevance of sustainable chemistry.